South Asians in the Diaspora, Histories and Religious Traditions. - Knut A. Jacobsen; Pratap Kumar (Editors) (Numen Book Series, 2004)
This volume deals with a phenomenon of increasing global significance, the South Asian diaspora. In particular it deals with the role of religion. The diversity of religious life in South Asia is remarkable and much of this diversity is replicated in the diaspora communities around the world. The case studies in this book explore and analyse the social, religious and cultural reality of people in the diaspora belonging to Jainism, Buddhism, Hinduism, Christianity, Islam, Sikhism and Zoroastrianism and originating from four of the South Asian nation states (India, Pakistan, Bangladesh and Sri Lanka). The book highlights the religious diversity that exists in the diaspora communities both across the traditions and within the particular religions.